Platelet and Leukocyte Concentration in Equine Autologous Conditioned Plasma Are Inversely Distributed by Layer and Are Not Affected by Centrifugation Rate - Radtke, Alexandra V.; Goodale, Margaret B.; Fortier, Lisa A. (Frontiers in Veterinary Science, 2020)
Background: Platelet rich plasma (PRP) is used extensively in equine regenerative medicine. Differences in preparation protocols give rise to significant variability in the cellular composition of PRP making it very difficult to establish a standard of care in the field. This study aimed to optimize the preparation protocol for leukocyte-reduced PRP (P-PRP). Methods: Blood (100 mL) was collected from horses (n = 5) and divided into 2 purple top EDTA tubes and 6 (15mL) double syringesa with a final concentration of 10% acid citrate dextrose anticoagulant. Six double syringesa were collected from each horse; PRP samples were prepared in duplicate and centrifuged at 1100 rpm (188xg), 1300 rpm (263xg), or 1500 rpm (350xg). Duplicates were subjected to +/- braking at the end of centrifugation. The total volume of PRP generated was measured and divided into thirds. Each third (top, middle, and bottom) were drawn off separately using the inner (6 mL syringe) and placed in purple top EDTA tubes. Automated complete blood counts were performed on all peripheral whole blood and PRP samples. Results: The concentration of leukocytes was higher in the bottom layer of PRP compared to the top and middle layers (p < 0.0001). The concentration of platelets was slightly lower in the bottom layer of PRP than the middle layer (p = 0.02). Centrifugation braking increased the leukocyte concentration in the top (p = 0.03) and middle layers of PRP (p = 0.001). Centrifugation rate had no effect on the cellular composition of PRP (p = 0.1 - 0.6). Conclusions: Because layer of plasma affected both platelet and leukocyte concentrations in PRP, the most important modification for the current single spin, double syringe, plasma based PRP preparation protocols is to exclude the bottom 1/3 layer of PRP.